The perception of gender and racial diversity in top management and its influence on employee engagement : a cross-sectional study of black women in South Africa’s financial services industry - Madziva, Tonderayi (University of Pretoria, 2025)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2024.